THE WORLD OF WARCRAFT : POP-UP BOOK - Reinhart, Matthew; Kafanov, Vladimir ([California] : BLIZZARD ENTERTAINMENT, 2019)
Choose your faction, pick your weapon, and prepare for an astonishing vision of the world of Azeroth through the lens of paper engineer Matthew Reinhart! The World of Warcraft pop-up book brings the most beloved locations of warcraft to life in a completely new way. The classic faction hubs of Orgrimmar and Stormwind, the battle-scarred lands of Lordaeron and Teldrassil, and even the new capital cities of Kul Tiras and Zandalar all unfold into an eye-popping treat, brimming with the brand-new art and interactive pieces. For a stunning finish, the entire book unfolds into a map of Azeroth!
Pop-up books.
Keywords: World of Warcraft (Game) -- Pictorial works -- Juvenile literature; Fantasy games; Lift-the-flap books; Toy and movable books; Picture books; Pop-up books -- Specimens